An Empirical Analysis on Effect of Cost Efficiency In Indian Industrial Banks: A study on cost efficiency and the impact of mergers in the Indian banking industry (Journal of Advances and Scholarly Researches in Allied Education, 2013)
This study assesses costefficiencies in the Indian banking industry for the period 2007 to 2011.Observational effects show that add up to cost and additionally working cost ofa bank is absolutely identified with the measure of the bank characterized asfar as holdings and deposits. This study demonstrates that sum cost and workingcost builds not exactly proportionately to build in holdings and deposits since2009, which indicates economies of scale with reference to stakes and deposits.Results likewise show that possession structure of a bank assumes a part inconfirming economies of scale in the Indian banking industry. Cost builds inthe private sector banks have been not exactly proportionate to builds instakes and deposits all around the example period. The present paperanalyzes the cost efficiency of Indian commercial banks by utilizing anon-parametric Data Envelopment Analysis Technique. The cost efficiencymeasures of banks are analyzed under both differentiate and normal boondocks.This paper likewise experimentally looks at the effect of mergers on the costefficiency of banks that have been united throughout post liberalizationperiod. The present study taking into account lopsided board information overthe period 1990-91 to 2007-08. In this paper to test the efficiencydistinctions between public and private both parametric and non-parametric testsare utilized. The discoveries of this study prescribe that over the whole studyperiod normal cost efficiency of public sector banks discovered to be 73.4furthermore for private sector banks is 76.3 percent. The discoveries of thispaper prescribe that to some degree merger programme has been fruitful inIndian banking sector. The Government and Policyproducers ought not advertise merger between solid and bothered banks as anapproach to advertise the premium of the depositors of upset banks, as it willhave unfavorable impact upon the possession nature of the stronger banks.